Connected gradings and fundamental group - Cibils, Claude (2010)
The main purpose of this paper is to provide explicit computations of the fundamental group of several algebras. For this purpose, given a k-algebra A, we consider the category of all connected gradings of A by a group G and we study the relation between gradings and Galois coverings. This theoretical tool gives information about the fundamental group of A, which allows its computation using complete lists of gradings.